Natural resource economics : theory and application in India - Kerr,Johyn M.(Editor) Marothia,Dinesh K.(Editor) Katar Singh(Editor) Ramasamy,C.(Editor) Bentley,William R.(Editor) (Oxford & IBH Pub. Co., 1997)
Contributed articles.